Supply Chain Determination of Business Continuity and Competitive Advantage - Cao Yujun (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This research discusses Supply Chain Determination towards Business Continuity and Competitive Advantage in Corner Yard Cafes. The purpose of this study is to find out whether the supply chain affects business continuity and creates a competitive advantage against the Courtyard Corner Cafe. The object of research is carried out in the Corner Café Courtyard. The population in this study was 93 respondents with a research sample of 30 respondents. The research method used is descriptive quantitative, which aims to determine how influential or not an object is both partially and simultaneously. The sampling method is carried out by the Accidential Sampling method. The tests carried out are the T Test, F Test and Coefficient of Determination. The results of this study include: 1) Supply Chain affects the Sustainability of the Yard Corner Café Business; 2) Supply Chain affects Competitive Advantage; and 3) Business Continuity affects Competitive Advantage.